Copper Iron Sulfide Nanocrystal‐Bulk Silicon Heterojunctions for Broadband Photodetection. Issue 9 (17th March 2020) - Sugathan, Anumol; Saigal, Nihit; Rajasekar, Guru Pratheep; Pandey, Anshu
Abstract: This study describes the optoelectronic characteristics of CuFeS2 /Si nanocrystal/bulk heterojunctions. These heterojunctions show a strong photocurrent response under ambient conditions upon excitation from a wide optical spectrum, from 460 to 2200 nm. The devices comprise of a heterojunction formed between heavily doped n‐type silicon (1–100 Ω cm) and copper iron sulfide (CuFeS2 ) nanocrystal films. Over the spectral range 460–2200 nm the device shows a fast response (20 µs at NIR wavelengths), along with responsivity and detectivity of 4.68 mA W −1 and 5.29 × 10 9 Jones at 1900 nm wavelength. The photocurrent is further observed to be a nonlinear function of power. These properties of the devices are discussed in terms of a defect filling mechanism. Besides their regular photoresponse described above, the devices also exhibit a slower photothermal response, allowing these to also sense hot objects (450 K; excess 6 mW incident onto the device) within the focal plane, thereby extending the useful sensing range of the devices deeper into the infrared. Abstract : CuFeS2 /n‐Si nanocrystal/bulk heterojunction photodetectors are prepared and their optoelectronic properties are studied. The photodetectors exhibit broadband photodetection (460–2200 nm) with fast response times (20 µs in the NIR). Different operation regimes are identified in the visible and NIR. Further, these detectors also possess a photothermal response that extends their sensitivity to thermal wavelengths.